2018
DOI: 10.1002/slct.201802048
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of a ZnO/PVA/β‐CD Composite Electrode for Rechargeable Zinc Anodes

Abstract: ZnO/PVA/β‐CD composite electrode was prepared by chemical crosslinking method. The FT‐IR spectrum of the composite electrode shows that the absorption peaks in 3379 cm−1 owing to the O−H stretching vibration decreased significantly, indicating the decreased of the hydroxyl number. The blue shift of the absorption peak at 3900 cm−1 owing to the O−H stretching vibration proves that the complex substance formed after cross‐linked reaction is more stable. Compared with the bare electrode, the cycle numbers of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Jo and coworkers 133 found that polyaniline-coated Zn could exhibit 85% corrosion inhibition efficiency relative to that of pure Zn and enable 97.81% capacity retention after 24 h storage in Zn-air batteries. PVA, a linear polyhydroxy polymer, has also been chosen as the coating material for protecting Zn anodes due to its film-forming capacity, hydrophilicity and easy chemical modification [134][135][136][137] . Zhang et al 134 reported a PVA layer crosslinked with a glutaraldehyde coater for enhancing the mechanical and chemical stability of Zn anodes.…”
Section: Polymer Coatingsmentioning
confidence: 99%
“…Jo and coworkers 133 found that polyaniline-coated Zn could exhibit 85% corrosion inhibition efficiency relative to that of pure Zn and enable 97.81% capacity retention after 24 h storage in Zn-air batteries. PVA, a linear polyhydroxy polymer, has also been chosen as the coating material for protecting Zn anodes due to its film-forming capacity, hydrophilicity and easy chemical modification [134][135][136][137] . Zhang et al 134 reported a PVA layer crosslinked with a glutaraldehyde coater for enhancing the mechanical and chemical stability of Zn anodes.…”
Section: Polymer Coatingsmentioning
confidence: 99%